Exploring the Socio-cultural and economic impacts of Dallagau Homestay on rural tourism in Nepal - Oli, Lok Bahadur (Journal of Jayaprithvi Multiple Campus, 2025)
The study titled 'Exploring the Socio-cultural impacts of Dallagau Homestay on rural tourism in Nepal' utilized a mix of qualitative and quantitative methods to examine the socio-cultural and economic benefits of rural tourism in Nepal. The research was specifically focused on Madhuban-1, Dallagau Homestay in the Bardiya District. It employed a descriptive-analytic approach within an exploratory research design, focusing on a purposively selected subset of 22 households out of 120 in Dallagau. Additionally, 22 non-homestay households and 22 recent visitors were also included in the study. Data were gathered from primary and secondary sources, including interviews with tourists, hoteliers, locals, tour guides, local politicians, and NGO representatives during a field survey in May 2024. Globally, the concept of "homestay" is interpreted differently, with each region having its unique version. In Nepal, homestay programs are community-driven initiatives that play a crucial role in the local economy and tourism sector. Despite the potential for substantial economic and socio-cultural benefits, the homestay industry in Nepal is hindered by inadequate infrastructure and planning. This research, focusing on the "Khata Biological Corridor Homestay" in Dalla village, emphasizes the socio-cultural and economic impacts of these programs. The findings underscore the importance of proper management and community involvement in maximizing the benefits of homestay tourism for sustainable rural development.